PENGARUH MULTIMEDIA INTERAKTIF TERHADAP KECEMASAN MATEMATIS DAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMPN 13 PADANG - Putra, Rhonaldo Perdana (Jurnal Edukasi dan Penelitian Matematika, 2023)
This research aims to analyze the impact of using interactive multimedia on students' mathematical anxiety and mathematical communication abilities. The study employs a One Group Pretest-Posttest Design, involving an experimental class without a control group. The research sample was selected using a purposive sampling technique from the 8th grade of SMPN 13 Padang in the Academic Year 2022/2023. The results show a significant influence of interactive multimedia on students' mathematical communication abilities, supported by the Paired Samples T-Test and N-Gain hypothesis tests. Most students experienced an improvement in their mathematical communication abilities, falling into the high and moderate categories. The same positive effect was observed regarding students' mathematical anxiety, as indicated by the Paired Samples T-Test and N-Gain tests. Most students showed a decrease in mathematical anxiety, falling into the high and moderate categories. Overall,  interactive multimedia has proven effective in enhancing students' mathematical communication abilities and reducing mathematical anxiety at SMPN 13 Padang. However, some limitations, such as generalization due to limited sample size, short treatment duration, and reliance on single multimedia, need attention. Further research is needed, involving more schools to better understand the influence of interactive multimedia on students' mathematical communication abilities and mathematical anxiety.Keywords – Interactive Multimedia, Mathematical Anxiety, Mathematical Communication